To simplify (25–√ + 37–√)2, we need to first expand the expression using the distributive property of multiplication over addition.
(25–√ + 37–√)2
= (25–√ + 37–√)(25–√ + 37–√)
= (25–√)(25–√) + (25–√)(37–√) + (37–√)(25–√) + (37–√)(37–√)
= 625 - 50√ + 25 + 925 - 37√ + 925 - 37√ + 1369
= 2914 - 124√
Therefore, the simplified expression is 2914 - 124√.
Question
Note: Enter your answer and show all the steps that you use to solve this problem in the space provided.
Simplify (25–√+37–√)2
. Show your work. Justify each step.
1 answer